2001
DOI: 10.1046/j.1365-2559.2001.01148.x
|View full text |Cite
|
Sign up to set email alerts
|

Follicular adenoma with papillary architecture: a lesion mimicking papillary thyroid carcinoma

Abstract: The papillary structures in the study cases are unlikely to represent degenerative changes due to their proliferative activity. In view of (i) the encapsulation and the uniformity of the constituent cells, (ii) the varying degrees of immunoreactivity for CK19 and HBME and negative immunoreactivity for Ret oncogene protein, and (iii) the absence or insufficiency of nuclear criteria for the diagnosis of PTC and the absence of lymph node metastasis in all study cases, we believe that these lesions represent the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 37 publications
2
38
0
Order By: Relevance
“…Some studies have reported that the papillary structure is a degenerative process in NG, but a hyperplasic process in thyroid adenoma 3 5. The markers of cell proliferation can be expressed in the papillary structures of benign tumours, which suggest that the papilla is formed by cell activation and proliferation 9 10. Our study determined that the expression of CK19, RET, galectin-3 and HBME-1 in PTC was higher than that in FA and NG.…”
Section: Discussionmentioning
confidence: 60%
“…Some studies have reported that the papillary structure is a degenerative process in NG, but a hyperplasic process in thyroid adenoma 3 5. The markers of cell proliferation can be expressed in the papillary structures of benign tumours, which suggest that the papilla is formed by cell activation and proliferation 9 10. Our study determined that the expression of CK19, RET, galectin-3 and HBME-1 in PTC was higher than that in FA and NG.…”
Section: Discussionmentioning
confidence: 60%
“…Furthermore, ret oncogene products have been identified in foci of LNFPTC. 24 Therefore, VI and distant metastasis are likely events in PTC, independent of Ret/PTC oncogene activation.…”
Section: Discussionmentioning
confidence: 99%
“…They were designated as adenomas with FIC, 20 neoplastic non-PTC lesion with FIC, 21 follicular adenoma with FIC and marked nuclear atypia, 22 non-infiltrating PTC 23 and adenoma with LNFPTC. 24 It is likely that these tumours did not have the potential of lymph node metastasis as compared with lesions diagnosed as PTC.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, cellularity and overlapping cytologic criteria in hyperplasia may lead to a false-positive diagnosis [73,74,75]. We accepted the suppressed role of papillary architecture without persuasive nuclear changes in diagnosing PTC proven in the series reported by Mai et al [89,90] although our own histopathologic experience includes rare cases of metastasizing papillary tumors without pronounced PTC nuclear features.…”
Section: Discussionmentioning
confidence: 87%